Small cortical infarcts: prevalence, determinants, and cognitive correlates in the general population. (4th June 2015) - Riba‐Llena, Iolanda; Koek, Marcel; Verhaaren, Benjamin F. J.; Vrooman, Henri A.; van der Lugt, Aad; Hofman, Albert; Ikram, M. Arfan; Vernooij, Meike W.
Abstract : Background: Cortical brain infarcts are defined as infarcts involving cortical gray matter, but may differ considerably in size. It is unknown whether small cortical infarcts have a similar clinical phenotype as larger counterparts. We investigated prevalence, determinants, and cognitive correlates of small cortical infarcts in the general population and compared these with large cortical infarcts and lacunar infarcts. Methods: Four thousand nine hundred five nondemented individuals (age 63·95 ± 10·99) from a population‐based study were included. Infarcts were rated on magnetic resonance imaging and participants were classified according to mean infarct diameter into small (≤15 mm in largest diameter) or large (>15 mm) cortical infarcts, lacunar infarcts, or a combination of subtypes. Spatial distribution maps were created for manually labeled small and large infarcts. Participants underwent cognitive testing. Analyses were performed using multinomial regression and analysis of covariance. Results: Three hundred eighty‐one (7·8%) persons had any infarct on magnetic resonance imaging, among whom 54 with small (1·1%) and 77 (1·6%) with large cortical infarcts. Small cortical infarcts were mainly localized in external watershed areas, whereas large cortical infarcts were localized primarily in large arterial territories. Age (odds ratio = 1·06; 95% confidence interval = 1·02, 1·09), male gender (1·98; 1·01, 3·92), and smoking (2·55; 1·06, 6·14) were determinants of small cortical infarcts. Participants with these infarcts had worse scores in delayed memory, processing speed, and attention tests than persons without infarcts, even after adjustment for cardiovascular risk factors. Conclusions: In the elderly, small cortical infarcts appear as frequent as large infarcts but in different localization. Our results suggest that small cortical infarcts share cardiovascular risk factors and cognitive correlates with large cortical, but also with lacunar infarcts.